Maxillofacial Injuries Due to Firearms (Ballistics) - Iriani Febrina; Antonius Winoto Suhartono; Almasyifa Herlingga Rahmasari Amin; Elza Ibrahim Auerkari (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Maxillofacial injuries caused by firearms can vary in severity and tissue damage, with the severity determined by the characteristics and nature of the bullet and the anatomical structures involved. The extent of tissue damage is also influenced by the distance from the shot. Injuries from low-velocity firearms result in less extensive damage compared to those caused by high-velocity firearms, where tissue damage may involve extensive hard and soft tissues, marked by a zone surrounding the damaged tissue vulnerable to progressive necrosis due to disrupted blood supply and wound sepsis. Review: For a physician, basic knowledge about firearms, ammunition composition, and the mechanism of firearm discharge is essential for proper understanding and interpretation of the resultant injuries or trauma. Firearms can be grouped based on barrel length, such as short-barreled firearms like revolvers and pistols, and long-barreled firearms like shotguns and rifles. Firearms can also be categorized based on their rifling, with rifled and non-rifled barrel firearms. Furthermore, firearms can be classified based on their bullet velocity, categorized as low-velocity firearms and high-velocity firearms. Conclusion: Maxillofacial injuries can vary in severity and tissue damage caused by firearms. Injuries caused by high-velocity firearms exhibit a greater degree of severity and tissue damage compared to those caused by low-velocity firearms. Infection prevention should involve early administration of penicillin antibiotics and early wound control by sealing the mucosa with waterproof materials.